SYSTEMATIC REVIEW KOMBINASI ORTOKERATOLOGI DENGAN ATROPIN PADA TERAPI MIOPIA ANAK - Melni Armadani; Rani Himayani; Syahrani Alya Murfi; Putu Ristyaning Ayu Sangging (Medula, 2023)
Myopia is a refractive disorder in which the light rays that enter the eye are focused in front of the retina, not directly above it, so that distant objects appear blurred. Based on several studies, it was found that myopia progresses most rapidly during childhood, and the age of stabilization has been reported to be in the 15-16 year age range. One of the therapies that can be used to slow the progression of myopia is atropine in combination with orthokeratology lenses. The research method was carried out by searching articles on PUBMED with the formula, namely 'Combination Orthokeratology with Atropine' AND 'Myopia' AND Children with a range of 2017 to 2023. Orthokeratology is a method that uses rigid contact lenses designed with a highly oxygen permeable return geometry that helps reshape the central cornea to correct low to moderate refractive errors. The efficiency of orthokeratology in reducing axial elongation in young children has been demonstrated worldwide. Atropine can block muscarinic receptors in the sclera and retina, resulting in thickening of the scleral fibrous layer and thinning of the scleral cartilage layer. This change retards axial elongation and results in recovery of the refractive error. From several existing literature studies, the combination of atropine therapy with orthokeratology lenses has proven effective in slowing the progression or development of myopia in children by suppressing axial elongation.